دور CRP سائل الجنب في تقييم شدة انصبابات الجنب المرافقة لذوات الرئة وتقرير العلاج المناسب - Hejazie, Malek; Yazigi, Haissam; Alhaj, Hiba (Latakia University Journal -Medical Sciences Series, 2019)
دور CRP سائل الجنب في تقييم شدة انصبابات الجنب المرافقة لذوات الرئة وتقرير العلاج المناسب مالك حجازية هيثم يازجي هبة الحاج مقدمة: يمثل انصباب الجنب المرافق لذوات الرئة سبباً هاماً لانصبابات الجنب النتحية، وتقدر نسبة الوفيات في انتانات الجنب ب20%[1] ، تتعلق نسبة الوفيات هذه بشكل أساسي بالتدبير غير المناسب للانصبابات.اذ لايزال تشخيص الانصباب المختلط الذي يحتاج للتداخل الجراحي يمثل تحدياً حقيقياً أمام اتخاذ القرار الأنسب للعلاج. الهدف: يهدف البحث الى تحديد دورCRP سائل الجنب بتقدير شدة الانصبابات المرافقة لذات الرئة ، وفي تقييم خصوصيته كمشعر لنزح السائل الجنبي بالأنبوب (تفجير الجنب). المرضى والطرق: دراسة مقطعية تحليلية شملت 67 مريضاً بالغاً من قبولات مشفى تشرين الجامعي في اللاذقية في الفترة الممتدة بين أيلول 2017 وتشرين الأول 2018، تم استبعاد 5 حالات تقيح جنب صريح. تم اجراء بزل الجنب بعد أخذ الموافقة المستنيرة وارسال العينات للدراسة الكيماوية وتحليل GLU و LDH و CRP. كما تم أخذ عينة لمعايرة الـ PH على جهاز غازات الدم . ثم تم تقسيم العينات الى انصباب جنب بسيط أو مختلط حسب العلاج المقترح من قبل الأخصائي المتابع للحالة. اعُتمد برنامج IBM SPSS statistics في تحليل البيانات واعتُبرت القيمة التنبؤية Pvalue الأقل من 0.05 هامة احصائياً. النتائج: أظهرت الدراسة أن قيمة الـ CRPفي سائل الجنب عند مرضى الانصباب المختلط (89.76±16.80 مغ/ل) كانت أعلى بفرق هام احصائياً بالمقارنة مع الانصباب البسيط (64.96±26.81 مغ/ل). وأنها عند قيمة حدية 73.5 مغ/ل كانت ذات دقة جيدة للتنبؤ بالحاجة الى التفجير الجنبي بالأنبوب. وقد أوجدت هذه الدراسة أن اجتماع المعايير التقليدية مع قيمة CRPpf هذه وفق قاعدة و/أو قد حسنت القيم التنبؤية الايجابية والسلبية على الترتيب. الخلاصة: لا يمكن للـ CRPpf أن يكون بديل عن PHpf في تشخيص الانصباب المختلط، لكنه يعتبر ذو دقة جيدة بهذا المجال خاصة عند جمعه مع المعايير التقليدية الأخرى الأقل أهمية من الـ PHpf لكن الأكثر توفراً كـ LDHpf وGLUpf. Background: parapneumonic effusion is an important reason of exudative effusions. mortality in pleural infection is 20%[1], this high rate is caused mainly by improper management of parapneumonic effusion , especially complicated parapneumonic effusion . especially that the identification of parapneumonic effusions (PPE) requiring pleural drainage is still challenging. Aim: to assess wether CRP in pleural fluid has a role in determining the severity of parapneumonic effusion ,and to evaluate its property as an indicator for drainage (complicated parapneumonic effusion). Materials and Methods: This was a Cross Sectional Analytic study conducted at Tishreen University Hospital, Lattakia, Syria, during period between September 2017 – October 2018 . It included 67 adults with PPE ,in which 5 patients with empyema were excluded. After informed consent was taken from each participant , a pleural thoracentesis was obtained and all the pleural fluid biomarkers were measured. The decision to drain pleural fluid at baseline was made by the attending physician. IBM SPSS statistics was used for data analysis . pvalue ˂ 0.05 was considered as statiatically significant. Results: This study showed that CRP in pleural fluid was significantly increased in CPPE (89.76±16.80 mg/l) as compaired with UPPE (64.96±26.81 mg/l). and that CRP at Cut-off point = 73.5 mg/l had a good accuracy in predicting the need of pleural drainage. A combination of classical biomarkers with CRP levels using an ‘AND’ or ‘OR’ rule improved the positive and negative predictive values, respectively. Conclusion: CRP in pleural fluid can not be a substitute for PH in determining the need of pleural drainage. Moreover, when used in combination with classical biomarkers, CRP levels may be a useful adjunct for decision-making in relation to treatment of patients with non-purulent PPE.